Do Inheritance Rules Affect Voter Turnout? Evidence from an Alpine Region - Andrea Bonoldi; Chiara Dalle Nogare; Martin Mosler; Niklas Potrafke (Center for Economic Studies and ifo Institute (CESifo), 2020)
We examine the relationship between inheritance rules and voter turnout. Inheritance rules are measured by entailed farms in South Tyrol: land properties whose inheritance is regulated by a law similar to the right of primogeniture. Using data for municipalities between 1998 and 2010, we show that voter turnout is high in municipalities with many entailed farms relative to population. The effect is based on local elections. If the number of entailed farms per 100 inhabitants increases by one standard deviation, voting turnout in municipal and provincial elections increases by around 1.27 and 1.43 percentage points (around 25 and 35 percent of a standard deviation). Our results suggest that entailed farm owners themselves are more likely to vote, and that entailed farms owners encourage other citizens of their municipality to participate in local elections.
Keywords: D72; H70; K11; Q15; Z19; 330; entailed farms; voter turnout; inheritance rules; identity; civic duty